High fructose corn syrup, excess-free-fructose, and risk of coronary heart disease among African Americans– the Jackson Heart Study - DeChristopher, Luanne R. (BMC Nutr, 2020)
BACKGROUND: Researchers have sought to explain the black-white coronary heart disease (CHD) mortality disparity that increased from near parity to ~ 30% between 1980 and 2010. Contributing factors include cardiovascular disease prevention and treatment disparities attributable to disparities in insurance coverage. Recent research suggests that dietary/environmental factors may be contributors to the disparity. Unabsorbed/luminal fructose alters gut bacterial load, composition and diversity. There is evidence that such microbiome disruptions promote hypertension and atherosclerosis. The heart-gut axis may, in part, explain the black-white CHD disparity, as fructose malabsorption prevalence is higher among African Americans. Between 1980 and 2010, consumption of excess-free-fructose–the fructose type that triggers malabsorption-exceeded dosages associated with fructose malabsorption (~ 5 g–10 g), as extrapolated from food availability data before subjective, retroactively-applied loss adjustments. This occurred due to an industrial preference shift from sucrose to high-fructose-corn-syrup (HFCS) that began ~ 1980. During this period, HFCS became the main sweetener in US soda. Importantly, there has been more fructose in HFCS than thought, as the fructose-to-glucose ratio in popular sodas (1.9-to-1 and 1.5-to-1) has exceeded generally-recognized-as-safe levels (1.2-to-1). Most natural foods contain a ~ 1-to-1 ratio. In one recent study, ≥5 times/wk. consumers of HFCS sweetened soda/fruit drinks/and apple juice-high excess-free-fructose beverages–were more likely to have CHD, than seldom/never consumers. METHODS: Jackson-Heart-Study data of African Americans was used to test the hypothesis that regular relative to low/infrequent intake of HFCS sweetened soda/fruit drinks increases CHD risk, but not orange juice-a low excess-free-fructose juice. Cox proportional hazards models were used to calculate hazard ratios using prospective data of 3407–3621 participants, aged 21–93 y (mean 55 y). RESULTS: African Americans who consumed HFCS sweetend soda 5-6x/wk. or any combination of HFCS sweetened soda and/or fruit drinks ≥3 times/day had ~ 2 (HR 2.08, 95% CI 1.03–4.20, P = 0.041) and 2.5–3 times higher CHD risk (HR 2.98, 95% CI 1.15–7.76; P = 0.025), respectively, than never/seldom consumers, independent of confounders. There were no associations with diet-soda or 100% orange-juice, which has a similar glycemic profile as HFCS sweetened soda, but contains a ~ 1:1 fructose-to-glucose ratio. CONCLUSION: The ubiquitous presence of HFCS in the food supply may pre-dispose African Americans to increased CHD risk.